2000
DOI: 10.1103/physrevd.62.065005
|View full text |Cite
|
Sign up to set email alerts
|

Ginzburg regime and its effects on topological defect formation

Abstract: The Ginzburg temperature has historically been proposed as the energy scale of formation of topological defects at a second order symmetry breaking phase transition. More recently alternative proposals which compute the time of formation of defects from the critical dynamics of the system [5], have been gaining both theoretical and experimental support. We investigate, using a canonical model for string formation, how these two pictures compare. In particular we show that prolonged exposure of a critical field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Many numerical simulations have been done within the framework of the Ginzburg-Landau model, [9][10][11][12][13] basically confirming the conclusions of the theory. In Ref.…”
supporting
confidence: 58%
“…Many numerical simulations have been done within the framework of the Ginzburg-Landau model, [9][10][11][12][13] basically confirming the conclusions of the theory. In Ref.…”
supporting
confidence: 58%
“…However, it gives enough reliable information on the critical-regime behavior. 1 We notice that in such an approximation 0 2 ϭϪm 2 . Let us now consider the expansion of the v field into partial waves…”
Section: The Ginzburg Regimementioning
confidence: 92%
“…Between T C and T G the system is said to be in the critical regime. 1 Our purpose is to model the time dependence of m 2 (␤) during the critical-regime evolution, i.e., for transitions lasting a finite time interval where the formation of domains is allowed.…”
Section: The Ginzburg Regimementioning
confidence: 99%
See 1 more Smart Citation
“…Historically the KZ mechanism has been at the centre of a debate about the timing of the birth of defects [61,62]. On one hand, it has been suggested that the appearance of defects can be traced to the fluctuations that freeze out at a timet before the transition occurs, i.e.…”
Section: When Is the Defect Density Determined?mentioning
confidence: 99%